Bereavement after sibling death: a population‐based longitudinal case‐control study. Issue 1 (February 2016) - Bolton, James M.; Au, Wendy; Chateau, Dan; Walld, Randy; Leslie, William D.; Enns, Jessica; Martens, Patricia J.; Katz, Laurence Y.; Logsetty, Sarvesh; Sareen, Jitender
Abstract : The objective of this study was to examine mental disorders and treatment use among bereaved siblings in the general population. Siblings (N=7243) of all deceased children in the population of Manitoba, Canada who died between 1984 and 2009 were matched 1:3 to control siblings (N=21, 729) who did not have a sibling die in the study period. Generalized estimating equations were used to compare the two sibling groups in the two years before and after the index child's death on physician‐diagnosed mental disorders and treatment utilization, with adjustment for confounding factors including pre‐existing mental illness. Analyses were stratified by age of the bereaved (<13 vs. 13+). Results revealed that, in the two years after the death of the child, bereaved siblings had significantly higher rates of mental disorders than control siblings, even after adjusting for pre‐existing mental illness. When comparing the effect of a child's death on younger versus older siblings, the rise in depression rates from pre‐death to post‐death was significantly higher for siblings aged under 13 (p<0.0001), increasing more than 7‐fold (adjusted relative rate, ARR=7.25, 95% CI: 3.65‐14.43). Bereaved siblings aged 13+ had substantial morbidity in the two years after the death: 25% were diagnosed with a mental disorder (vs. 17% of controls), and they had higher rates of almost all mental disorder outcomes compared to controls, including twice the rate of suicide attempts (ARR=2.01, 95% CI: 1.29‐3.12). Siblings in the bereaved cohort had higher rates of alcohol and drug use disorders already before the death of their sibling. In conclusion, the death of a child is associated with considerable mental disorder burden among surviving siblings. Pre‐existing health problems and social disadvantage do not fully account for the increase in mental disorder rates.